O impacto do projeto setorial integrado de promoção de exportações de café sobre o processo de internacionalização e a competitividade de empresas fabricantes de café torrado e/ou moído - Oura, Maurício Massao (2008)
The purpose of this study was to assess the impact of the Brazilian export consortium Projeto Setorial Integrado de Promoção de Exportações de Café (PSI) on the internationalization process and competitiveness of manufacturers of Roasted and/or Ground coffee (R&G). For this analysis, the internationalization theories and models of competitive advantage - Resource-Based View of the Firm and Industry Analysis Framework - have been considered. To reach this goal, we searched: (i) to raise the historical context of the coffee in Brazil and worldwide; (ii) to describe the trajectory of the process of internationalization of the Brazilian manufacturers of R&G; (iii) to assess the PSI objectives for increasing the competitiveness of its participants outside Brazil, comparing them with the results obtained by the interviewed companies. Concerning the research design, we utilized an embedded single-case study. The results of the interviews with the PSI managers and with four coffee roasting companies evidence the low contribution of the project for the insertion of such companies into the international market.